Membangun LINGKAR (Literasi Digital untuk Anak Pintar) sejak Dini di SDN Mranggon Lawang II Probolinggo - Dzaky Isyuniandri; Indani Khoirun Nisak (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service activity is to improve the digital literacy of children at SDN Mranggon Lawang II by teaching them how to find accurate information and know the dangers of hoaxes. In order for children to use technology wisely, they must be taught important digital literacy from an early age. This activity was carried out through interactive lectures and Q&A discussions for seven days in August 2024. In addition to examples of simple false information, the material includes differences of opinion and facts, there were 13 children who participated showing a high level of enthusiasm during the activity. However, there are obstacles regarding language that hinder understanding that can be overcome through communication techniques and visual media. The results of the activity show that children better understand the importance of critical thinking when getting information. This activity is expected to increase knowledge about digital literacy and encourage smart media behavior.